Efek Loading Statin Intensitas Tinggi Sebelum Intervensi Koroner Perkutan pada Pasien Sindrom Koroner Akut: Systematic Review - Suwari, Cokorda Istri Padmi; Claudia, Mutiara (Jurnal Kesehatan Andalas, 2024)
Percutaneous Coronary Intervention (PCI) is one of the essential methods for Acute Coronary Syndrome (ACS) treatment, but this procedure has serious complications. Early loading dose statin has a favorable prognostic impact on patients undergoing PCI. However, this effect is still unclear.Objective: To evaluated the effect of loading high-intensity statin on Major Adverse Cardiac Events (MACE) before PCI in patients with ACS. Methods: Randomized controlled trials were conducted using databases fromÂ  CENTRAL, PubMed, Science Direct, and British Medical Journal. Then, titles, abstracts, and full texts were screened using the inclusion criteria to filter out irrelevant studies. Quality assessments were undertaken using the Jadad scale, and the results were narratively synthesized and presented in tables. Results: Seven studies were included in this systematic review after screening 1037 records. Four studies demonstrated a statistically significant reduction in MACE in the groups that received loading dose atorvastatin or rosuvastatin before PCI, compared with the comparator groups (p < 0.05). Conclusion: Loading high-intensity statin before PCI seems to be highly effective in reducing MACE in patients with ACS.Keywords: Â acute coronary syndrome, major adverse cardiac events, percutaneous coronary interventionÂ